The efficacy of N-acetylcysteine as a hepatoprotective agent in liver transplantation - Thies, Jochen; Teklote, Jörg-Rudolf; Clauer, Ulf; Töx, Ulrich; Klar, Ernst; Hofmann, Walter J.; Herfarth, Christian; Otto, Gerd (Transplant international, 1998)
One of the most common complications after liver transplantation is primary graft dysfunction which results from severe deterioration of the microcirculation. The data obtained from our experimental studies indicate that N-acetylcysteine (NAC) is able to reduce the severity of ischemia/reperfusion injury and improves postoperative graft function after liver transplantation in rats. The aim of this pilot study was to evaluate the efficacy of NAC as a hepatoprotective agent under clinical conditions. A group of 30 liver transplanted patients were treated with NAC, and 30 patients (control group) were treated with a 5 % solution of glucose only. In the NAC group we observed a distinct reduction in ischemia/reperfusion injury and improved liver function with less elevated peak transaminases, better macrocirculation, improved liver synthesis function and a lower incidence of primary nonfunction compared with the control group. We conclude that NAC is a very promising substance for reducing graft dysfunction in clinical liver transplantation.